An analysis of selected regulatory shortcomings that affect the Master of the High Court's ability to execute its duties as the insolvency regulatory of South Africa - Van Wyk, Jani Sani (University of Pretoria, 2023)
Mini Dissertation (LLM (Mercantile Law))--University of Pretoria, 2022.